Overexpression of the aldehyde dehydrogenase AhALDH3H1 from Arachis hypogaea in soybean increases saline-alkali stress tolerance - Cao, Yingxue; Wang, Jing; Zhao, Siqi; Fang, Qingxi; Ruan, Jingwen; Li, Shuanglin; Liu, Tongxin; Qi, Yuxin; Zhang, Ling; Zhang, Xiaoming; Meng, Fanli (Frontiers in Plant Science, 2023)
Soybean production is severely hampered by saline-alkaline stress caused by saline-alkalization. Plants have aldehydrogenase (ALDH) family members that convert reactive aldehydes to carboxylic acids to remove active aldehyde molecules. However, little is known about the increased saline-alkali tolerance caused by the ALDH function in soybean. Here, we introduced a previously identified ALDH coding gene AhALDH3H1 from Arachis hypogaea into the soybean genome to investigate its critical role in response to saline-alkali stress. Transgenic soybean with increased aldehyde dehydrogenase activity showed significant tolerance to saline-alkali stress. It reduced malondialdehyde (MDA) content compared to its receptor, suggesting that over-expression of AhALDH3H1 accelerated soybean tolerance to saline-alkali stress by increasing aldehyde dehydrogenase activity, which is responsible for scavenging toxic MDA. To further analyze the inner mechanisms that allow transgenic plants to tolerate saline-alkali stress, we sequenced the transcriptome and metabolome of P3 (wild type, WT) and transgenic lines which were separately treated with water and a saline-alkali solution. When subjected to saline-alkali stress, the integrated analysis of the transcriptome and metabolome suggested that several genes related to cell wall structure crucial for preserving cell wall extensibility and plasticity were largely responsible for restoring homeostasis within the transgenic cells compared to WT. Metabolites, including both necessary ingredients for cell wall genesis and harmful production produced during the saline-alkali stress response, could be transported efficiently with the help of the ABC transporter, reducing the negative effects of saline-alkali stress. These findings suggest that introducing AhALDH3H1 increases transgenic soybean tolerance to saline-alkali stress may through cell wall structure maintenance and metabolites transport.